Left Ventricular Diastolic Dysfunction in Peritoneal Dialysis. Issue 20 (May 2015) - Wu, Cho-Kai; Lee, Jen-Kuang; Wu, Yi-Fan; Tsai, Chia-Ti; Chiang, Fu-Tien; Hwang, Juey-Jen; Lin, Jiunn-Lee; Hung, Kuan-Yu; Huang, Jenq-Wen; Lin, Jou-Wei; Hou., Xuwei
<x xml:space="preserve">Abstract</x> Abstract Left ventricular diastolic dysfunction (LVDD) is common among patients undergoing peritoneal dialysis (PD). We examined the relationship between LVDD, major adverse cardiovascular events (MACE), and mortality in PD patients. A total of 149 patients undergoing PD with preserved left ventricular systolic function were included and followed for 3.5 years. LVDD was diagnosed (according to the European Society of Cardiology guidelines) by conventional and tissue Doppler echocardiography. Serum high-sensitivity C-reactive protein (hsCRP) was measured. The location and volume of adipose tissue were assessed by computed tomography (CT) at the level of the fourth lumbar vertebra. Subjects with LVDD had higher levels of hsCRP, and more visceral and peritoneal fat than controls. The relationship between adjusted visceral adipose tissue and LVDD became nonsignificant when hsCRP and baseline demographic data were introduced into the logistic regression model (odds ratio = 1.52, P = 0.07). Subsequent hierarchical multivariate Cox regression analysis showed that LVDD was one of the most powerful determinants of MACE and mortality after adjusting for all confounding factors (hazard ratio [HR]: 1.71, 95% confidence interval [CI]: 1.43–3.51, P = 0.02 and HR: 2.25, 95% CI: 1.45–2.91, P = 0.04, respectively). Systemic inflammation (hsCRP) was also significantly associated with MACE and mortality (HR: 2.03, P = 0.03 and HR: 2.16, P = 0.04, respectively). LVDD is associated with systemic inflammation and increased visceral fat in patients undergoing PD. LVDD is also a sensitive, independent indicator of future MACE and mortality in PD patients.